Hubungan Tingkat Stres Terhadap Perubahan Hemodinamik Pada Pasien Gagal Jantung - Dianita, Eka Mei; Priyanti, Ratna Puji; Khoiri, Ahmad Nur; Permana, Arief Candra; Imam, Nurul; Sari, Purwanti Nurvita (Jurnal Keperawatan Muhammadiyah, 2025)
Objective: Heart failure is the number one cause of death from non-communicable diseases every year, which is caused by impaired heart and blood vessel function. In Indonesia, the prevalence continues to increase every year. One of the psychological factors for morbidity and mortality in heart failure patients is stress. High levels of stress have a negative impact on the development of heart failure. Methods: The purpose of this study was to determine the relationship between stress levels and hemodynamics in heart failure patients. This type of research is quantitative descriptive, using a cross-sectional data collection method. The number of respondents was 109 respondents in the heart polyclinic of Bangil Hospital using a purposive sampling technique. The research instrument used a questionnaire, PSS (Perceived Stress Scale) to measure stress levels and hemodynamic status measured including blood pressure, respiration. The hemodynamic instrument uses observations of blood pressure results using an automatic digital omron device and patient respiration by observing the condition and symmetry of respiratory movements. Data analysis used chi-square. Results: The results showed that heart failure patients experienced moderate stress levels of 78.9% and grade 1 hypertension blood pressure of 44.8%. In addition, heart failure patients experienced moderate stress levels and normal pulses of 95.4%. Conclusion: The conclusion of this study is that stress levels are related to blood pressure and pulse in heart failure patients.